Combination of structured illumination and single molecule localization microscopy in one setup - Roßberger, Sabrina; Best, Gerrit; Baddeley, David; Heintzmann, Rainer; Birk, Udo J.; Dithmar, Stefan; Cremer, Christoph (Journal of optics, 2013)
Understanding the positional and structural aspects of biological nanostructures simultaneously is as much a challenge as a desideratum. In recent years, highly accurate (20 nm) positional information of optically isolated targets down to the nanometer range has been obtained using single molecule localization microscopy (SMLM), while highly resolved (100 nm) spatial information has been achieved using structured illumination microscopy (SIM). In this paper, we present a high-resolution fluorescence microscope setup which combines the advantages of SMLM with SIM in order to provide high-precision localization and structural information in a single setup. Furthermore, the combination of the wide-field SIM image with the SMLM data allows us to identify artifacts produced during the visualization process of SMLM data, and potentially also during the reconstruction process of SIM images. We describe the SMLM-SIM combo and software, and apply the instrument in a first proof-of-principle to the same region of H3K293 cells to achieve SIM images with high structural resolution (in the 100 nm range) in overlay with the highly accurate position information of localized single fluorophores. Thus, with its robust control software, efficient switching between the SMLM and SIM mode, fully automated and user-friendly acquisition and evaluation software, the SMLM-SIM combo is superior over existing solutions.
Gesehen am 20.01.2022